Implementation of Academic Supervision Teacher Performance at SDN Baros Mandiri 7 - Mutiah, Enung (Journal Of Education And Teaching Learning (JETL), 2023)
The implementation of academic supervision as a manifestation of improving the quality of educational management conducted by the school principal becomes essential to be carried out. Therefore, this research aims to determine the implementation of academic supervision on the performance of teachers at SDN Baros Mandiri 7. The research method used is School Action Research (SAR) with data collection techniques through observation, questionnaires, and documentation aimed at classroom teachers and subject teachers. The data analysis technique used is quantitative descriptive analysis. The research results show that the implementation of academic supervision at SDN Baros Mandiri 7 in cycles 1 and 2 experienced an overall improvement from the "sufficient" category to "good," with the average score for classroom teacher performance increasing from 67.4 to 86.4 and subject teacher performance from 63.5 to 78.6. However, it was also found that classroom teacher performance and subject teacher performance had differences in certain indicators. Therefore, improving teacher performance through academic supervision is crucial to be done continuously, including enhancing collaboration among teachers and the need for support from the school principal in the form of training and facilities for educational management at the school.